Influence of regional cerebral blood volume on voxel-based morphometry - Zheng, Lei; Vollmayr, Barbara; Hesser, Jürgen; Sartorius, Alexander (NMR in biomedicine, 2016)
The investigation of structural brain alterations is one focus in research of brain diseases like depression. Voxel-based morphometry (VBM) based on high-resolution 3D MRI images is a widely used non-invasive tool for such investigations. However, the result of VBM might be sensitive to local physiological parameters such as regional cerebral blood volume (rCBV) changes. In order to investigate whether rCBV changes may contribute to variation in VBM, we performed analyses in a study with the congenital learned helplessness (cLH) model for long-term findings. The 3D structural and rCBV data were acquired with T2-weighted rapid acquisition with relaxation enhancement (RARE) pulse sequences. The group effects were determined by standard statistical parametric mapping (SPM) and biological parametric mapping (BPM) and examined further using atlas-based regions. In our genetic animal model of depression, we found co-occurrence of differences in gray matter volume and rCBV, while there was no evidence of significant interaction between both. However, the multimodal analysis showed similar gray matter differences compared with the standard VBM approach. Our data corroborate the idea that two group VBM differences might not be influenced by rCBV differences in genetically different strains.